Digital health technologies to support access to medicines and pharmaceutical services in the achievement of sustainable development goals. (May 2018) - Konduri, Niranjan; Aboagye-Nyame, Francis; Mabirizi, David; Hoppenworth, Kim; Kibria, Mohammad Golam; Doumbia, Seydou; Williams, Lucilo; Mazibuko, Greatjoy
Objectives: The objective of this study was to describe the conceptual and implementation approach of selected digital health technologies that were tailored in various resource-constrained countries. To provide insights from a donor-funded project implementer perspective on the practical aspects based on local context and recommendations on future directions. Methods: Drawing from our multi-year institutional experience in more than 20 high disease-burden countries that aspire to meet the 2030 United Nations Sustainable Development Goal 3, we screened internal project documentation on various digital health tools that provide clarity in the conceptual and implementation approach. Taking into account geographic diversity, we provide a descriptive review of five selected case studies from Bangladesh (Asia), Mali (Francophone Africa), Uganda (East Africa), Mozambique (Lusophone Africa), and Namibia (Southern Africa). Findings: A key lesson learned is to harness and build on existing governance structures. The use of data for decision-making at all levels needs to be cultivated and sustained through multi-stakeholder partnerships. The next phase of information management development is to build systems for triangulation of data from patients, commodities, geomapping, and other parameters of the pharmaceutical system. A well-defined research agenda must be developed to determine the effectiveness of the country- and regional-level dashboards as an early warning system to mitigate stock-outs and wastage of medicines and commodities. Conclusion: The level of engagement with users and stakeholders was resource-intensive and required an iterative process to ensure successful implementation. Ensuring user acceptance, ownership, and a culture of data use for decision-making takes time and effort to build human resource capacity. For future United Nations voluntary national reviews, countries and global stakeholders must establish appropriate measurement frameworks to enable the compilation of disaggregated data on Sustainable Development Goal 3 indicators as a precondition to fully realize the potential of digital health technologies.